The Relationship between Physician and Nurses' Burnout and Stress Levels and Healthy Lifestyle Behavior in the COVID‐19 Pandemic. - Ozcoban, Kardelen; Altunkurek, Şeyma Zehra; Greco, Gianpiero (Perspectives in Psychiatric Care, 2024)
Background. In this study, we aimed to evaluate the relationships between burnout among doctors and nurses and stress levels and healthy lifestyle behaviors during the COVID‐19 pandemic. Methods. The study was carried out as a cross‐sectional design. The sample consisted of 258 nurses and doctors working at Ankara University Faculty of Medicine Cebeci Research and Application Hospital. Data were collected between April and October 2021 using a sociodemographic form, the Burnout Measure Short Version (BMS), the Perceived Stress Scale (PSS), and the Healthy Lifestyle Behaviors Scale‐II (HLBS‐II). T tests, one‐way analysis of variance (ANOVA), and post hoc (Tukey, LSD) analyses were used to analyze the descriptive characteristics and scale scores of the participants. Spearman's correlation analysis was used to examine the relationships between scale scores and continuous data. Regression analysis was performed to define the reason and result relationship between the scales. Results. As a result of the correlation analysis, a positive, moderate relationship was found between the participants' PSS total scores and BMS total scores (p < 0.05). There was a moderate and weak statistically significant relationship between the participants' PSS and BMS total score average and HLBS‐II total score and subdimensions (p < 0.05). In addition, it was determined that there was a statistically significant and negative correlation between the participants' PSS and BMS total score average and the HLBS‐II total score and subdimensions (p < 0.05). After the regression analysis, the relationship between the reason and the result among the total PSS, BMS, and HLBS‐II scores was found to be significant (p < 0.05). Conclusions. The results obtained from this study revealed that the rising burnout and stress levels of nurses and doctors during the pandemic decreased the level of healthy lifestyle behaviors and led them to use negative coping methods.